Female asthma and atopy – impact on fertility: a systematic review - Bláfoss, Joan (J Asthma Allergy, 2019)
BACKGROUND AND OBJECTIVE: Asthma is one of the most common chronic diseases among women of reproductive age, and previous studies have suggested a link between female asthma and infertility. The aim of the present review is to provide an update on current knowledge of the association between female asthma and/or atopy and a reduction in fertility, ie, number of offspring, time to pregnancy (TTP) and need for fertility treatment. METHODS: Systematic review performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-guidelines. RESULTS: A total of 14 studies fulfilled the predefined criteria for inclusion in the present review. Six studies investigated the association between female asthma and/or atopy and number of offspring, of which one reported a positive, two a negative, and three no association. Three studies addressed the association between asthma and TTP and found that TTP was significantly prolonged in asthmatic women compared to non-asthmatic women. Five studies investigated subfertility and the need for fertility treatments of which two studies found a higher prevalence of infertility among women prescribed anti-asthma medication. One study found no difference in the number of fertility treatments of asthmatic women compared to non-asthmatic women, whereas three studies reported that female asthma was associated with significantly more fertility treatment compared to non-asthmatic women. CONCLUSION: Although the available evidence is conflicting, there is a clear trend toward an association between female asthma and a reduction in fertility, and by that a larger proportion requiring fertility treatment, even though female asthma might not negatively affect total number of offspring.